Family Coping Strategies in Autism Spectrum Disorder: An Integrative Review - Campos, Cristiane Soares; Anna Cláudia Yokoyama dos Anjos, Juliana Pena Porto (International Journal of Innovative Research in Medical Science, 2016)
Objective: The purpose of this study was to collect and evaluate scientific productions and integrate research results about challenges and coping strategies of families with people with Autism Spectrum Disorder (ASD). Method: Through the integrative review, the data collection was performed using the descriptors "autistic disorder", "autism", "autistic disorder", and "family" in the databases SCIELO, BDENF, LILACS, PubMed and MEDLINE. Results: Four articles were selected for the final sample of this work. The main challenges identified by the families were the impact of the diagnosis and educational difficulties. Coping strategies used were social media, blogs creation, searching for different health professionals, family adaptability, looking for support in faith, and involvement in parents' associations. Conclusion: Few articles were found, which highlights the importance of the study in this topic and gives relevant information to facilitate health care and coaching of health professionals.